(untitled) (American Journal of Business Management, Economics and Banking, 2024)
Green logistics has emerged as a critical area for sustainable development worldwide, and Uzbekistan is no exception. Given the growing environmental concerns and Uzbekistan’s strategic position in Central Asia, implementing green logistics practices could significantly reduce emissions, improve energy efficiency, and enhance economic resilience. This article examines the opportunities and challenges associated with advancing green logistics in Uzbekistan, highlighting strategic approaches for integrating sustainable practices into the country’s logistics sector. By analyzing policy frameworks, technological innovations, and infrastructure needs, this study identifies the key factors that could drive green logistics in Uzbekistan and discusses potential obstacles to successful implementation. Ultimately, a sustainable logistics strategy can contribute to Uzbekistan’s environmental goals while promoting long-term economic growth.